Plasmonic Sensor Nata de Coco Film Inserted with Copper Nanoparticles for Detection of Mercury by UV-Vis Spectrophotometry - Watoni, Abdul Haris Haris; Rijal, Rijal; Ramadhan, La Ode Ahmad Nur; Kadir, La Ode Abdul (Departemen Kimia, 2025)
The rapid development of the mining industry has resulted in an increasing amount of toxic waste materials in the environment, including mercury (Hg). A reliable chemical sensor is needed to detect the presence of mercury. One of the chemical sensors that is starting to be widely developed is plasmonic film. This research aims to determine the characteristics and validity of plasmonic nata de coco-copper nanoparticle (CuNPs) films for cuvette type sensor chips in the rapid detection of Hg metal using UV-Vis spectrophotometry. This research began with the preparation of a bioreductor from red dragon fruit peel extract, green synthesis of CuNPs, synthesis of nata de coco, and synthesis of nata de coco-cellulose plasmonic film inserted with CuNPs-red dragon fruit peel extract. The next stage is the validation and application of plasmonic films for Hg metal detection using UV-Vis spectrophotometry. The success of this research was proven through characterization using an Ultra Violet-Visible (UV-Vis) spectrophotometer, a Fourier Transform Infra Red (FTIR) spectrophotometer, and a digital optical microscope. UV-Vis spectrophotometric analysis showed the formation of stable CuNPs with a diameter of 46 nm - 92 nm. FTIR analysis shows changes in functional groups in the red dragon fruit peel extract compound, nata de coco cellulose, and the formation of Cu-O bonds as an indication that the process of reducing Cu2+ ions to Cu0 has occurred and the insertion of CuNPs-red dragon fruit peel extract in the nata de coco cellulose film matrix. Analysis using an optical microscope shows the morphology of CuNPs with a uniform round shape. Measurement of the Hg standard solution using UV-Vis spectrophotometry in a cuvette inserted with a plasmonic film has good accuracy and precision with %R = 103.9% and %RSD = 0.9%, with LOD and LOQ values of 0.193 ppm and 0.245 ppm, respectively. The use of plasmonic film in determining Hg using UV-Vis spectrophotometry was proven more sensitive than without plasmonic film with a sensitivity value of 1.50. These results indicate that the pasmonic film from nata de coco-CuNPs has the potential to be applied as a cuvette type sensor chip for Hg metal detection.